Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1055/s-2005-865747
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA Response of Triathletes Participating in the French Iron Tour

Abstract: Athletes are susceptible to upper respiratory tract infections (URTI) during intense training and after major competitions. Secretory IgA, which is the predominant antibody of the mucosal immune system, is the major effector of host-resistance to many microorganisms causing URTI. Previous studies have shown that salivary IgA-mediated immunity decreases after a single short distance triathlon, but the effect of repeated triathlon competitions on secretory IgA levels remains unknown. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 22 publications
(36 reference statements)
1
21
0
6
Order By: Relevance
“…Immune function has been shown to be less impaired in highly conditioned versus sedentary elderly subjects [21] suggesting that aerobic conditioning may be benefi cial to immune health in older adults. Several papers have been published regarding the infl uence of exercise in mucosal and plasma antibodies concentration [1,7,9,14,16,22,24,26,27,30,33,35,36,39,44,45] . The lack of consistency in fi ndings supports the need for more studies to further our understanding of this aspect of immune regulation.…”
Section: Eff Ects Of Aerobic Conditioning On Salivary Iga and Plasma mentioning
confidence: 99%
“…Immune function has been shown to be less impaired in highly conditioned versus sedentary elderly subjects [21] suggesting that aerobic conditioning may be benefi cial to immune health in older adults. Several papers have been published regarding the infl uence of exercise in mucosal and plasma antibodies concentration [1,7,9,14,16,22,24,26,27,30,33,35,36,39,44,45] . The lack of consistency in fi ndings supports the need for more studies to further our understanding of this aspect of immune regulation.…”
Section: Eff Ects Of Aerobic Conditioning On Salivary Iga and Plasma mentioning
confidence: 99%
“…1 It has been reported that acute highintensity exercise and long-term heavy training lead to a decrease in immune functions. [2][3][4][5] Additionally, Nieman has reported that people who habitually do moderate exercise have less risk of URTI than those people who do not; however, he also has reported that high-intensity exercise increases the risk of URTI. 6 Since it is known that URTI adversely affects training and performance, 7 it is important for athletes to avoid URTI in order to maintain a good physical and mental condition.…”
Section: Introductionmentioning
confidence: 99%
“…A liberação de no-raepinefrina observada durante o exercício prolongado está associada à redução do fluxo salivar (34) , que, por sua vez, diminui as concentrações de IgA na saliva. Garantir um bom nível de secreção salivar, mesmo durante o exercício, é fundamental para impedir reduções acentuadas nos níveis de IgA-s. Uma forma interessante de assegurar isso é manter o indivíduo hidratado.…”
Section: Produção Salivarunclassified
“…Estudos encontraram reduções na concentração de IgA tanto durante como após um período prolongado de treinamento intenso no ciclismo (32,35) , na corrida (24) , na natação (47) , no triátlon (48) e em atletas de caiaque (49) . Libicz et al (34) investigaram oito triatletas durante o Iron Tour da França e coletaram, diariamente, amostras de saliva quando os atletas acordavam, antes da etapa do dia e após cada dia de competição. O fluxo salivar foi significantemente menor após cada etapa, comparada com o estado basal.…”
Section: Exercício De Intensidade Altaunclassified
See 1 more Smart Citation